Electronic energy structure of the (100) In4Se3 surfaces at different preparation and treatment in ultraviolet photoelectron spectroscopy study - Makar, T.R.; Dzyuba, V.I.; Nenchuk, T.M.; Tuziak, O.Ya.; Galiy, P.V. (Physics and Chemistry of Solid State, 2024)
The (100) surface of In4Se3 layered crystal was obtained in situ, ions sputtered and exposed to UHV for hours. The UPS spectra for these surfaces, atomically clean, and after the mentioned treatments, were recorded and analyzed to obtain electronic spectra of In4Se3 (100) surface. The first-principles calculations were performed by DFT-GGA method, and for the In4Se3 underestimated (0.21 eV) band gap was attained. The calculated total density of states of In4Se3 in general coincides with a UPS spectrum for an atomically clean cleaved surface. Thus the study of the band structure of (100) In4Se3 cleavage surfaces after the ion sputtering or exposure to UHV for more than several hours is uninformative, and such effects on the sample should be avoided.